2023
DOI: 10.1101/2023.12.21.572809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reward Expectation Reduces Representational Drift in the Hippocampus

Seetha Krishnan,
Mark E.J. Sheffield

Abstract: SummarySpatial memory in the hippocampus involves dynamic neural patterns that change over days, termed representational drift. While drift may aid memory updating, excessive drift could impede retrieval. Memory retrieval is influenced by reward expectation during encoding, so we hypothesized that diminished reward expectation would exacerbate representational drift. We found that high reward expectation limited drift, with CA1 representations on one day gradually re-emerging over successive trials the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
(124 reference statements)
1
4
0
Order By: Relevance
“…Importantly, this study examined drift on a shorter 4-day time-scale than the ∼ 30 days that we considered. Our study is nevertheless consistent with the results from 17 in the sense that both conclude that reward is a strong driver of drift dynamics.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Importantly, this study examined drift on a shorter 4-day time-scale than the ∼ 30 days that we considered. Our study is nevertheless consistent with the results from 17 in the sense that both conclude that reward is a strong driver of drift dynamics.…”
Section: Discussionsupporting
confidence: 91%
“…Here, we distinguished between both different aspects of active experience and replayed experience. Another recent study using two-photon calcium imaging of hippocampal neural populations in rats performing a navigational task found that drift was slow when reward expectation was high, and lowering the animals' reward expectation sped up representational drift 17 . Importantly, this study examined drift on a shorter 4-day time-scale than the ∼ 30 days that we considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4) It should differentially affect place fields with distinct retained durations to result in the convergently growing retention probability (Figures 5C and 5D). Memory must be selected for long-term storage, with more valuable experiences, such as those related to rewards [66][67][68] , being more likely to be stabilized. From a computational perspective, RD delineates the process of neuronal representations optimizing toward an optimal solution 31 , which theoretically exhibits convergent dynamics 56 .…”
Section: Discussionmentioning
confidence: 99%